2021
DOI: 10.4317/jced.58930
|View full text |Cite
|
Sign up to set email alerts
|

Implant insertion angle and depth: Peri-implant bone stress analysis by the finite element method

Abstract: Background The study aimed to assess the influence of different implant insertion angles and depths on the stresses produced on the surface of peri-implant bone tissue under axial and oblique loading. Material and Methods The entire study followed the recommendations of the Checklist for Reporting In-vitro Studies (CRIS). The implant was placed in the region of element 36, according to the following models: M1 (0 mm / 0°); M2 (0 mm / 17°); M3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“… 35 A greater difference between the implant angle and the long axis angle of the tooth results in a greater stress value. 36 The results of this study showed that the mean long axis angle of the maxillary first premolars was significantly larger than that of the second premolars, as reported in a previous study. 3 The angle between the tooth axis and the alveolar bone axis is influenced by the root position, and buccally positioned teeth show the largest angulation.…”
Section: Discussionsupporting
confidence: 85%
“… 35 A greater difference between the implant angle and the long axis angle of the tooth results in a greater stress value. 36 The results of this study showed that the mean long axis angle of the maxillary first premolars was significantly larger than that of the second premolars, as reported in a previous study. 3 The angle between the tooth axis and the alveolar bone axis is influenced by the root position, and buccally positioned teeth show the largest angulation.…”
Section: Discussionsupporting
confidence: 85%
“…Factors such as the diameter and length of the implant, placement location, leftright angles, front-rear angles, Young's modulus of the cancellous bone, and thickness of the cortical bone can affect implants [23][24][25][26][27]. The effect and stability of each of these factors should be determined because they can introduce variations in the results such as osseointegration.…”
Section: Introductionmentioning
confidence: 99%